2019
DOI: 10.1038/s41545-019-0042-1
|View full text |Cite
|
Sign up to set email alerts
|

Removal of pepper mild mottle virus by full-scale microfiltration and slow sand filtration plants

Abstract: It is important to evaluate the removal of enteric viruses by drinking water treatment processes so that viral infection risk can be assessed and managed. However, evaluating the removal of enteric viruses by full-scale treatment processes can be challenging due to the low numbers of viruses and the presence of substances in the water samples that inhibit detection. In this study, we evaluated the removal of pepper mild mottle virus (PMMoV) by microfiltration (MF) and slow sand filtration (SSF) at two full-sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…The removal ratios of PMMoV, as evaluated by PCR, have been shown to be similar to or smaller than those of human enteric viruses in laboratory-scale coagulation-rapid sand filtration or membrane filtration processes (Shirasaki et al, 2017a;Kato et al, 2018;Shirasaki et al, 2018). Also, virus removal efficiencies in actual drinking water treatment plants have successfully been determined by targeting indigenous PMMoV due to its high concentration in drinking water sources (Kato et al, 2018;Canh et al, 2019). Therefore, if the inactivation efficiencies of PMMoV and human enteric viruses are comparable, PMMoV could be a useful surrogate for evaluating the efficacy of disinfection processes for the inactivation of human enteric viruses.…”
Section: Introductionmentioning
confidence: 99%
“…The removal ratios of PMMoV, as evaluated by PCR, have been shown to be similar to or smaller than those of human enteric viruses in laboratory-scale coagulation-rapid sand filtration or membrane filtration processes (Shirasaki et al, 2017a;Kato et al, 2018;Shirasaki et al, 2018). Also, virus removal efficiencies in actual drinking water treatment plants have successfully been determined by targeting indigenous PMMoV due to its high concentration in drinking water sources (Kato et al, 2018;Canh et al, 2019). Therefore, if the inactivation efficiencies of PMMoV and human enteric viruses are comparable, PMMoV could be a useful surrogate for evaluating the efficacy of disinfection processes for the inactivation of human enteric viruses.…”
Section: Introductionmentioning
confidence: 99%
“…CC-BY-ND 4.0 International license available under a Similarly, greater removal of crAssphage than PMMoV was previously reported (Tandukar et al, 2020), although the concentrations of both viruses decreased (3.3 ± 1.0 and 2.0 ± 0.4 for crAssphage and PMMoV, respectively). The different LRV between Tandukar et al (Tandukar et al, 2020) and this study may be related to different treatment systems and/or water temperatures (Canh et al, 2019). It is also possible that different water sample processing between WWTP effluent and influent samples (i.e., with and without ultrafiltration, respectively) could have influenced the recovery of viral particles results in this study.…”
Section: Discussionmentioning
confidence: 67%
“…Similar to this study, greater removal of crAssphage than PMMoV was previously reported, although the concentrations of both viruses decreased (3.3 ± 1.0 and 2.0 ± 0.4 for crAssphage and PMMoV, respectively). The different LRV between Tandukar et al and this study may be related to different treatment systems and/or water temperatures . It is also possible that different water sample processing between WWTP effluent and influent samples could have influenced the recovery of viral particle results in this study.…”
Section: Resultsmentioning
confidence: 99%